Actor Relation In The Dynamic of Inter-Regional Cooperation Policy (Case Study: Development Program of Metropolitan Area of Banjar Bakula, South Kalimantan Province) - Taufik Abrain (Iapa Proceedings Conference, 2018)
Several studies have shown that the success in the inter-regional cooperation was influenced by coordination, commitment, participation, variance of cooperation, structure and format of as a factor that contributes the determinant in the successful cooperation between regions. This research was a qualitative research, conducted on the object of policy of inter-regional cooperation Banjarbakula Program, South Kalimantan Province, February 2017-February The result of this study states that the success of cooperation to political will. In fact these factors did not stand alone since the aspect of actor relationship as the determinant aspect drove those factors effectively. This article aims to examine the aspect of actor relationship cooperation between regions was influenced by the dynamics of actor relationships in constructing factors as suggested by the previous experts. The actors involved in the inter- regional cooperation became the triggers of coordination, commitment and participation to the success and failure, as well as the effectiveness of regional cooperation policy. Structural obstacles, ego-centric, minimally budget and no visionary planning could be overcome as long as the dynamics of actor relationships were managed properly.